Penile traction therapy and Peyronie's disease: a state of art review of the current literature. (February 2013) - Chung, Eric; Brock, Gerald
In recent years, penile traction therapy (PTT) has gained considerable interest as a novel nonsurgical treatment option for men with Peyronie's disease (PD) and short penises. The current published literature suggests that selected cases of PD may benefit from a conservative approach with PTT, resulting in increased penile length and reduction of penile deformity. It appears to be safe and well tolerated but requires a great deal of patient compliance and determination. This article reviews the current literature pertaining to the use of PTT in men with PD, short penises and in the setting of pre- and postprosthesis corporal fibrosis.